Improving SNR and Sensitivity for Low-Coupling EMT Sensors - Zili Zhang; Ziqi Chen; Jianxin Xu; Wuliang Yin (IEEE Open Journal of Instrumentation and Measurement)
Electromagnetic tomography (EMT), also known as magnetic inductance tomography (MIT) is a tomographic modality widely employed in process industry and biomedical applications. In particular, this technique plays an important role in imaging metallic objects since it can produce conductivity and permeability distributions in the region of interest. An EMT system consists of a coil array, a data acquisition system, and an imaging reconstruction computer. Coils are used to generate electromagnetic field which interacts with the objects under investigation and measure the induced voltages. Conventionally, coils with sufficient inductance coupling (considerable number of turns or dimensions) are used to achieve high sensitivity and good SNR performance. However, this poses limitations for some applications, such as high-temperature applications and small-scale facilities. In high-temperature applications such as in steel or copper production processes, coils of the large number of turns are more likely to be damaged due to the breakdown of insulating materials between the turns, resulting in measuring errors. Besides, EMT applied in small-scale facility requires sensors with reduced dimensions, which results in weak magnetic coupling and lower SNR. In order to address these issues, this article proposes a method to transform the impedance and hence increase the sensor signal level through designing boosting transformers. Simulation and experimental results suggest that this increases the system SNR and image stability.